Temperature Change When Drilling Near the Distal Femoral Physis in a Skeletally Immature Ovine Model. Issue 7 (October 2016) - Tenfelde, Allison M.; Esquivel, Amanda O.; Cracchiolo, Allison M.; Lemos, Stephen E.
Abstract : Background: The possibility of physeal injury during anterior cruciate ligament reconstruction in the pediatric population is a concern. The purpose of this study was to determine whether drilling at or near the physis could cause a temperature increase that could trigger chondrolysis. Methods: Skeletally immature cadaveric lamb distal femurs were used for this study and randomly placed in 1 of 6 groups (n=10 in each group). We examined the 8 and 10 mm Flipcutter at a distance of 0.5 mm from the physis and an 8 and 10 mm acorn-tipped reamer at a distance of 0.5 and 3.0 mm from the physis. During drilling, temperature change at the distal femoral physis was continuously measured until the temperature decreased to the original value. Results: An interreamer comparison yielded a significant difference when drilling 0.5 mm from the physis ( P =0.001). Pair-wise Mann-Whitney post hoc tests were performed to further evaluate the differences among the groups. The 8 mm FlipCutter had a significantly higher maximum temperature (39.8±1.4°C) compared with the 10 mm FlipCutter (38.0±0.6°C, P =0.001), 8 mm acorn-tipped reamer (38.1±0.9°C, P =0.007), and 10 mm acorn-tipped reamer (37.5±0.3°C, P <0.001). Conclusions: The risk of thermal-induced injury to the physis is low with an all epiphyseal drilling technique, when a traditional acorn-tipped reamer over a guidepin is utilized, even if the drilling occurs very close to the physis. In addition, the risk of drilling with a FlipCutter is low, but may be greater than a traditional reamer. Clinical Relevance: Thermal-induced necrosis is a realistic concern, due to the characteristics of the distal femoral physis, and the propensity for this physis to respond poorly to injury. Our study supports that drilling near the physis can be done safely, although smaller reamers and nontraditional designs may generate higher heat. Level of Evidence: Level I—basic science.